UBE3A and Its Link With Autism - Vatsa, Naman; Jana, Nihar Ranjan (Frontiers in Molecular Neuroscience, 2018)
UBE3A is a dual function protein consisting of ubiquitin ligase as well as transcriptional co-activator function. UBE3A gene is imprinted in the brain with preferential maternal-specific expression particularly in the neuron and loss of activity of the maternally inherited UBE3A causes Angelman syndrome (AS), characterized by severe mental retardation, lack of speech, seizures and autistic features. Interestingly, duplication, triplication or gain-of-function mutations in the UBE3A gene are also linked with autism clinically distinguished by social impairments and stereotyped behaviours. These findings indicate that the expression and activity of UBE3A must be tightly regulated during brain development and UBE3A might be playing a crucial role in controlling synaptic function and plasticity through proteasome-mediated degradation as well as transcriptional regulation of its target proteins. In fact, several recent reports demonstrated the role of UBE3A in the modulation of synaptic function and plasticity. This review focused on the critical role of UBE3A in regulating the synaptic function and how its altered activity is associated with autism.